Peningkatan Throughput Produksi Manufaktur dengan Simulasi DES dan Teknik Optimasi Taguchi - Diki Muchtar (Sekolah Tinggi Teknologi Wastukancana, 2026)
Improving throughput in production is one of the main challenges in manufacturing systems. This study aims to enhance throughput by using Discrete Event Simulation (DES) combined with the Taguchi optimization technique to identify key factors influencing production performance. The simulation was conducted on a manufacturing production system with three tested factors: X1, X2, and X3, as well as two main responses: throughput (Y1) and bottleneck (Y2). Based on the simulation results, it was found that an increase in factor X3 significantly contributed to throughput improvement, while simultaneously reducing the bottleneck percentage, indicating better efficiency in the production line. For example, in experiment run 7 (X1 = 3, X2 = 0.4, X3 = 0.4), throughput reached 3,525 pieces, with a very low bottleneck percentage of 9.66%. Other simulation results also showed throughput improvements with reduced bottleneck, such as in runs 8 and 9, which had throughput of 3,524 pieces and 2,936 pieces, with bottleneck percentages of 19.66% and 15.66%, respectively, showing more optimal results. The Taguchi optimization technique was used to minimize variability and improve the quality of the production system output. The results of this study indicate that the combination of DES simulation and Taguchi optimization successfully increased production throughput significantly while reducing bottlenecks in the production process. This study contributes to the application of simulation and optimization in improving production efficiency in the manufacturing industry, with the hope that it can be adapted to various types of production systems.